Mengukur viabilitas serbuk sari dan sukrosa terhadap perkecambahan Swainsona formosa (G.Don) J.Thompson - Z, Zulkarnain (Biospecies, 2019)
The work presented here was aimed at investigating the proper time (after spreading) for viability assessment and the effect of various sucrose concentrations on pollen germination in Swainsona formosa. The rate of pollen tube formation was determined for freshly shed pollen grains of glasshouse-grown plants at 10, 15, 20, 25, 30, 60 and 120-minute intervals after being plated on Brewbaker and Kwack (BK) medium. The results indicated that within 60 minutes pollen germination reached 63.70%, after which remained steady at 120 minutes (63.71%). Under the effect of various concentrations of sucrose, i.e. 0.5, 10, 15, and 20% (w/v), the germination rate of pollen grains was assessed at 60 minutes following germination. The results showed that sucrose concentration of 10 – 15% (w/v) produced better germination rate (64.14%) compare to lower concentrations (19.64 and 43.58% at zero and 5% sucrose, respectively). Sucrose concentration above 15% was also found to inhibit pollen germination (48.92% at sucrose concentration of 20%).